High Level Expression of Recombinant Human Tissue Factor in Chinese Hamster Ovary Cells as a Human Thromboplastin - Rehemtulla, Alnawaz; Pepe, Michael; Edgington, Thomas S (Thrombosis and Haemostasis, 1991)
Tissue factor (TF) is the high affinity transmembrane receptor and cofactor for cellular initiation of the plasma coagulation protease cascades by factor VIIa. We describe the synthesis of recombinant huTF by stably transfected CHO cell lines carrying integrated huTF DNA, and the isolation of huTF glycoprotein with specific functional activity equivalent to natural huTF, The expression vector (pCDM8), carrying the cytomegalovirus promoter to drive transcription of a partial cDNA construct encoding the complete huTF protein chain, was cotransfected with a plasmid containing the neomycin resistance gene for selection. These clones were further selected for level of expression of huTF protein. Optimal expression compatible with stability and cell growth was approximately 13.5 x 106 molecules per cell. To our knowledge, this is one of the highest levels of expression described for a recombinant transmembrane receptor in mammalian cells. Recombinant huTF protein was obtained by single-step immuno-affinity purification, and exhibits heterogeneity due to N-linked glycosylation. The protein was indistinguishable from natural huTF based on functional properties of the glycoprotein reconstituted in lipid vesicles, and expression of conformational epitopes. Large scale production of recombinant huTF is feasible to permit basic studies of protein structure as well as for design of huTF thromboplastin reagents.